Endoskeletal mineralization in chimaera and a comparative guide to tessellated cartilage in chondrichthyan fishes (sharks, rays and chimaera). Issue 171 (28th October 2020) - Seidel, Ronald; Blumer, Michael; Chaumel, Júlia; Amini, Shahrouz; Dean, Mason N.
Abstract : An accepted uniting character of modern cartilaginous fishes (sharks, rays, chimaera) is the presence of a mineralized, skeletal crust, tiled by numerous minute plates called tesserae. Tesserae have, however, never been demonstrated in modern chimaera and it is debated whether the skeleton mineralizes at all. We show for the first time that tessellated cartilage was not lost in chimaera, as has been previously postulated, and is in many ways similar to that of sharks and rays. Tesserae in Chimaera monstrosa are less regular in shape and size in comparison to the general scheme of polygonal tesserae in sharks and rays, yet share several features with them. For example, Chimaera tesserae, like those of elasmobranchs, possess both intertesseral joints (unmineralized regions, where fibrous tissue links adjacent tesserae) and recurring patterns of local mineral density variation (e.g. Liesegang lines, hypermineralized 'spokes'), reflecting periodic accretion of mineral at tesseral edges as tesserae grow. Chimaera monstrosa 's tesserae, however, appear to lack the internal cell networks that characterize tesserae in elasmobranchs, indicating fundamental differences among chondrichthyan groups in how calcification is controlled. By compiling and comparing recent ultrastructure data on tesserae, we also provide a synthesized, up-to-date and comparative glossary on tessellated cartilage, as well as a perspective on the current state of research into the topic, offering benchmark context for future research into modern and extinct vertebrate skeletal tissues.